A Pragmatic Study On English Jokes About Marriage In Internet - Rofik, Ahmad (2012)
This study is a pragmatic study. The objectives of this study are: (1) to describe the intentions of the jokes on marriage in internet, (2) to find the implicatures of the jokes on marriage in internet, and (3) to find the violation on Grice's maxims in humor about marriage in internet. This research is a descriptive qualitative study. The object of this research is English jokes about marriage in internet. The data used are written jokes. The source of this data is taken from http://www.ahajokes.com. The writer used documentation method in collecting data. To find the speaker intentions the writer used speech act theory. In finding the Grice's maxim violation the writer used Cooperative Principles Theory. And in finding the implicatures he used the theory of context of speech and implicatures. This study shows four results. 1) The representative speech act are applied to express speaker intentions as (1) expressing feeling, (2) informing, (3) alluding, (4) suggesting, (5) insulting, (6) accusing, and (7) classifying. The directive speech act are applied to express the intention of (1) commanding, (2) requesting, (3) responding, (4) claiming, (5) teasing, (6) suggesting, and (7) asking. The commissive speech act are used to express the intention of (1) asking and (2) informing. 2) There are two types of implicature shown in the data; they are (1) conversational implicature and (2) scalar implicature. The conversational implicatures are mostly used while the scalar implicatures are presentend in two data, 19 and 28. 3) The Grice's maxim violation occurs in four maxims; they are (1) Quality maxim, which its violation occurs when the speaker lacks evidence and gives untrue information to the hearer. (2) Quantity maxim which is violated by giving less or more information than needed. (3) Manner maxim which its violation rises in humor text if the speaker let his/ her utterance ambiguous and (4) Relation maxims which is violated by making the speaker's utterance irrelevant to the topic of speaking.